2018
DOI: 10.31014/aior.1992.01.04.50
|View full text |Cite
|
Sign up to set email alerts
|

Do The Earnings Management, Governance, Media Exposure, and Ownership Structure Have Any Effect on ESG Disclosure?

Abstract: The Journal of Economics and Business is an Open Access publication. It may be read, copied and distributed free of charge according to the conditions of the Creative Commons Attribution 4.0 International license.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
(99 reference statements)
0
1
0
Order By: Relevance
“…However, some studies have found that due to the value discovery and creation functions of ESG information, executives may use ESG disclosure to “self‐promote” to enhance the positive public evaluation of the firms (Adiasih et al, 2018; Hur et al, 2018) and ultimately establish a good image and maintain a good reputation, which is essentially a strategic choice in ESG disclosure (Li & Zheng, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies have found that due to the value discovery and creation functions of ESG information, executives may use ESG disclosure to “self‐promote” to enhance the positive public evaluation of the firms (Adiasih et al, 2018; Hur et al, 2018) and ultimately establish a good image and maintain a good reputation, which is essentially a strategic choice in ESG disclosure (Li & Zheng, 2012).…”
Section: Introductionmentioning
confidence: 99%